Analysis Of The Use Of X-Means Method In Grouping Interest And Talent Data Students - Purwa Hasan Putra; Muhammad Syahputra Novelan (Jurnal Ipteks Terapan, 2020)
The X-Means algorithm is an algorithm used for grouping data. The x means algorithm is the development of k-means. X-means clustering is used to solve one of the main weaknesses of K-means clustering, namely the need for prior knowledge about the number of clusters (K). In this method, the true value of K is estimated in an unsupervised way and only based on the data set itself. The research results using the X-Means algorithm with Davies-Bouldin Index evaluation Determination of the number of Centroid clusters is done by modifying the X-Means method. In grouping this data, clustering is performed on each student data of the collected variables. Each student's gift and interest will be matched with the college and department of what each student is interested in